The tiger : a true story of vengeance and survival - Vaillant, John (Alfred A. Knopf, 2010)
It's December 1997, and a man-eating tiger is on the prowl outside a remote village in Russia's Far East. The tiger isn't just killing people, it's annihilating them, and a team of men and their dogs must hunt it on foot through the forest in the brutal cold. Injured, starving, and extremely dangerous, the tiger must be found before it strikes again. As he re-creates these extraordinary events, John Vaillant gives an unforgettable portrait of this spectacularly beautiful and mysterious region. We meet the native tribes who for centuries have worshipped and lived alongside tigers, even sharing their kills with them. We witness the arrival of Russian settlers in the nineteenth and early twentieth centuries, soldiers and hunters who greatly diminished the tiger populations. And we come to know their descendants, who, crushed by poverty, have turned to poaching and further upset the natural balance of the region.